Analisa Struktur Pelimpah Bendungan Lubuk Ambacang Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi Provinsi Riau - Nur Sholawatini; Evi Nur Cahya; Heri Suprijanto (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
Lubuk Ambacang Dam is Roller Compact Concrete Dams and located on the Indragiri River, where the overflow spillway structure also important part of the dam. The purpose of this study is to find out the critical area in the structure when an earthquake occurs. Hydraulic analysis determine the appropriate spillway width. Stability analysis is find out that the planned structure is safe from overturning and sliding. The bearing capacity of the soil is also analyzed to determine whether the soil structure has sufficient capacity to withstand the structure load. Structure load are analyzed in normal conditions, Operating Basic Earthquake (OBE) and Maximum Design Earthquake (MDE). Planned of spillway structure based on the analysis of shell plates using STAADPro V8i application. Result of this study, spillway width is 51 meters which is safe from overturning and sliding. Bearing capacity of the soil is able to withstand the structure stress. The results of STAAD.Pro V8i show that the spillway critical area occurs in the upstream part of spillway when the reservoir water conditions are normal and when the OBE occurs. Whereas the Probable Maximum Flood (PMF) condition, critical area is in chuteway channel. For the stilling basin, the critical area occurs in the upper structure when the conditions are Q100th, 1.25Q100th normal and during an OBE.